CONCEPT “LAUGHTER”AS ONE OF THE BASIC LINGUO-COGNITIVE STRUCTURAL UNITS IN THE MODERN UKRAINIAN PROSE, POETRY, DRAMA AT THE BEGINNING OF XXI CENTURY - Danyliuk, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The semantic and structural features of the language means represented concept “laugh” in Ukrainian artistic discourse at the beginning of the XXI century is analyzes in the article; their role in the addresserrecipient relations, communication strategies and tactics in fiction has been defined, the specific features of their verbalization in remarks and replicas of drama have been researched, associative and imaginative potential and features of compatibility has been analyzed; the functional load of linguistic units, its representation in prose texts, drama and poetry have been analyzed.